Establecer las caracteristicas de Bienestar Psicologico y Bienestar Material entre 24 mujeres participantes del programa de voluntariado Manos a la Obra del Banco de Alimentos y de otro grupo de no voluntarios (2019)
The objective of this research is to determine the differences in Psychological Wellbeing and Material Well-being among 24 women participating in the Hands-on-Work volunteer program of the Food Bank and another group of non-volunteers.